Smoldering multiple myeloma – Past, present, and future. (March 2022) - Mann, Hashim; Katiyar, Vatsala; Varga, Cindy; Comenzo, Raymond L.
Abstract: Smoldering multiple myeloma (SMM) routinely precedes the development of multiple myeloma. While some patients experience aggressive disease, others have more indolent courses akin to those with monoclonal gammopathy of undetermined significance. Much effort has been made to understand the pathobiological basis of this heterogeneity. Scientific advancements have led to the emergence of various clinical and genomic markers of relevance, translating into evolution of disease definitions over time. More recently, the interest in manipulation of biological pathways has intensified in a bid to stall or halt disease progression. Studies with lenalidomide have exemplified the promise of early intervention, whereas numerous therapeutic approaches remain the subject of ongoing clinical investigation. This review summarizes the historic progress made in defining SMM as a distinct clinicopathologic entity, provides a critical appraisal of the evidence guiding risk assessment, and suggests a pragmatic approach to its modern-day management. Finally, an overview of developments on the horizon is also provided.